PENGARUH KOMPENSASI FINANSIAL DAN STRES KERJA TERHADAP KEPUASAN KERJA KARYAWAN (Studi pada Karyawan bagian Produksi PT Daya Anugrah Mandiri).” - Ardinal Djalil; Wiara Sanchia Grafita Ryana Devi (Ekonam: Jurnal Ekonomi, Akuntansi & Manajemen, 2020)
Human resources are the key to achieving company goals, therefore human resource management must be carried out appropriately so that company activities are not hampered, one of the things that companies must pay attention to is employee job satisfaction because high job satisfaction will make employees enthusiastic at work and capable. give the best for the company. While job dissatisfaction can make employee morale low, and make discipline and turnover relatively large, this in turn will prevent company activities from running effectively and efficiently. Job satisfaction is inseparable from the factors that can affect employee job satisfaction, some of which are financial compensation and job stress. Among the ways to determine employee job satisfaction is to know the state of financial compensation and work stress at the Head Office of PT Daya Anugrah Mandiri The purpose of this study was to determine whether there is an effect of financial compensation and job stress on employee job satisfaction either partially or simultaneously. The population in this study were 29 employees at the Head Office of PT Daya Anugrah Mandiri where the entire population was used as the object of research using saturated sampling. The variables studied in this study were job satisfaction, financial compensation, job stress. The method used in this research is a quantitative method with descriptive and verification approaches, and for data collection using survey methods, namely, questionnaires and interviews. The data collected is then analyzed using frequency distribution tables, classical assumption tests, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis and determination coefficient analysis, with the help of a computerized system (SPSS version 16.0). The results of the research and discussion show: (1) Job satisfaction is in the low category with a total score of 1117, financial compensation is in the poor category with a total score of 741, and job stress is in the high enough category with a total score of 901. (2) Partially, the effect of financial compensation on job satisfaction is very strong with the contribution of the influence of 78.7% and the remaining 21.3% is influenced by other factors. The effect of job stress is very strong on job satisfaction with the contribution of the influence of 78.5% and the remaining 21.5% is influenced by other factors. (3) Simultaneously, the influence of financial compensation and job stress is very strong with the contribution of the influence of 87.5% and the remaining 12.5% ​​is influenced by other factors.